2014
DOI: 10.1039/c4ra04921g
|View full text |Cite|
|
Sign up to set email alerts
|

DFT/TDDFT insights into the chemistry, biochemistry and photophysics of copper coordination compounds

Abstract: Highlighting the recent progress in DFT/TDDFT application to coordination chemistry of copper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 182 publications
(151 reference statements)
0
13
0
Order By: Relevance
“…Finally, we conclude that B3LYP seems to serve as a good starting point for the electronic structure calculations of the present charge‐transfer systems which are of considerable size. In the literature, B3LYP is discussed ambiguously: on the one hand, this “workhorse” of quantum chemistry yields astonishingly good energetic and optical predictions with small basis sets and is hence extremely widely used; on the other hand, it suffers from severe shortcomings such as increasing energetic errors with increasing molecular size and sometimes unreliability for transition metal systems . Ramos et al found that B3LYP is an average performing functional for small copper complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we conclude that B3LYP seems to serve as a good starting point for the electronic structure calculations of the present charge‐transfer systems which are of considerable size. In the literature, B3LYP is discussed ambiguously: on the one hand, this “workhorse” of quantum chemistry yields astonishingly good energetic and optical predictions with small basis sets and is hence extremely widely used; on the other hand, it suffers from severe shortcomings such as increasing energetic errors with increasing molecular size and sometimes unreliability for transition metal systems . Ramos et al found that B3LYP is an average performing functional for small copper complexes.…”
Section: Resultsmentioning
confidence: 99%
“…[Color figure can be viewed in the online issue, which is available at wileyonlinelibrary.com.] sets and is hence extremely widely used [81][82][83][84][85][86] ; on the other hand, it suffers from severe shortcomings such as increasing energetic errors with increasing molecular size and sometimes unreliability for transition metal systems. [81] Ramos et al found that B3LYP is an average performing functional for small copper complexes.…”
Section: Full Papermentioning
confidence: 99%
“…[24,25] Figure 4d shows the XPS spectra of the Cu corroles as compared to Cu-2 and [TBA][Cu(CF 3 ) 4 ], [26] which were studied as authentic Cu II To complement spectroscopic experiments,D FT calculations (B3LYP/6-311G(d,p) with toluene CPCM solvation) were performed for Cu-1 as ac losed shell 1 Cu(III) singlet, af erromagnetically coupled 3 Cu(II) corrole radical cation, and an antiferromagnetically coupled, broken symmetry 1 Cu(II) corrole radical cation (Tables S3-S5, Figure S7 and S8). TheB 3LYP functional has been used to study aw ide variety of copper complexes [28] and it has been shown for copper corroles to give the most accurate values of DE T-S when benchmarked against pure functionals or multiconfigurational methods. [11] As ab enchmark, energies were also computed for optimized structures using Complete Active Space Multiconfiguration SCF (CASSCF).…”
Section: An Authentic Cumentioning
confidence: 99%
“…The quantum calculations, in particular density functional theory (DFT), are widely used in coordination chemistry not only to achieve a quantitative description of * Corresponding author. Email: sa_zarei@iausdj.ac.ir, Seyedamirzarei@yahoo.com chemical and physical features of different complexes but also to predict new physical and chemical features [16][17][18][19][20][21]. Rigamonti et al reported the DFT calculation of the copper complexes of some salen-type ligands to confirm the assignments of electronic absorption spectra and evaluate the NLO properties [22].…”
Section: Introductionmentioning
confidence: 96%